Purification and Properties of Extracellular Endoinulinase from Aspergillus niger 20 OSM - Marcin Skowronek; Jan Fiedurek (Food Technology and Biotechnology, 2006)
Extracellular inulinase (E.C. 3.2.1.7) produced by Aspergillus niger 20 OSM culture in a 2-litre fermentor was isolated and purified by ion exchange chromatography on DEAE Sepharose, hydrophobic interaction on phenyl Sepharose, chromatofocusing on PBE-94, and size exclusion chromatography (SEC) on Sephadex G-200. The enzyme was homogeneous, as measured by SDS-PAGE with an apparent molecular mass of 69 or 64 kDa, as determined by SEC. Carbohydrate content of the enzyme was estimated at approx. 44.5 %. The optimum temperature and pH for enzyme activity were 55 oC and 5.0, respectively. Some physicochemical properties of the purified inulinase were also determined (isoelectric point, Km, Vmax and Ea). Enzyme activity was inhibited by EDTA, pCMB, Hg2+, Mn2+, and some other metal ions. Calcium cations showed a positive effect on the enzyme activity. Thin layer chromatography indicated that the purified enzyme is a typical endoinulinase.